Fiction to film :Ruth Prawer Jhabvala's The householder and Heat and dust - Vivek Sachdeva (Orient Blackswan, 2017)
Examining the relationship between literature and cinema from the perspective of structuralism narrative theory, this book studies how different kinds of narratives change during adaptation and offers an alternative model for the study of narratives. It addresses issues of cinematic adaptation and asks: what changes take place in a narrative when a novel is adapted into film? Looking at the art forms of novel, theatre and film, and the evolution of narratology as a discipline, It also shows how narratological tools, used to study literary texts, are equally relevant and applicable to the study of cinematic narratives